Factors affecting the uptake of community-based health insurance in Ethiopia: a systematic review - Bayked, Ewunetie M.; Kahissay, Mesfin H.; Workneh, Birhanu D. (International Journal of Scientific Reports, 2021)
The goal of health care financing in Ethiopia is achieving universal health care coverage by community-based health insurance which was expected to cover more than eighty percent of the population. The aim was to minimize catastrophic out-of-pocket health service expenditure. We systematically reviewed factors affecting the uptake of community-based health insurance in Ethiopia. We searched various databases by 09 to 10 March 2019. We included articles regardless of their publication status with both quantitative and qualitative approaches. The factors determining the uptake of community-based health insurance in Ethiopia were found to be demographic and socio-economic, and health status, and health service-related issues. Among demographic and socio-economic factors, the report of the studies regarding gender and age was not consistent. However, income, education, community participation, marriage, occupation, and family size were found to be significant predictors and were positively related to the uptake of the scheme. Concerning health status and health service-related factors; illness experience, benefit package, awareness level, previous out of pocket expenditure for health care service, and health service status (quality, adequacy, efficiency, and coverage) were significantly and positively related but the premium amount, self-rated health status and bureaucratic complexity were found to be negative predictors. To achieve universal health care coverage through community-based health insurance, special attention should be given to community-based intervention.